Adoptive transfer of immature myeloid cells lacking NF‐κB p50 (p50‐IMC) impedes the growth of MHC‐matched high‐risk neuroblastoma. Issue 7 (2nd May 2021) - Cui, Cheng; Barberi, Theresa; Suresh, Rahul; Friedman, Alan D.
Abstract : High‐risk neuroblastomas harbor abundant myeloid cells that suppress antitumor immunity and support tumor growth. Macrophages lacking the inhibitory NF‐κB p50 subunit adopt a pro‐inflammatory phenotype. We now report that murine 9464D neuroblastoma cells, which express high levels of exogenous MYCN, grow slower in syngeneic p50(f/f);Lys‐Cre mice that lack p50 in macrophages and neutrophils, compared with p50(f/f) littermates. Tumors in p50(f/f);Lys‐Cre mice possess increased numbers of total and activated CD4 + and CD8 + T cells, and depletion of both of these T‐cell populations accelerates tumor growth. Anti‐PD‐1 T‐cell checkpoint blockade, or DNA methyltransferase and histone deacetylase inhibition, further slows tumor growth. In addition, adoptive transfer of immature myeloid cells lacking NF‐κB p50 (p50‐IMC), generated either from the bone marrow of p50 −/− mice or via nucleofection of a p50 sgRNA:Cas9 complex into wild‐type hematopoietic progenitors, also slowed growth of MHC‐matched 9464D tumors but not of MHC‐mismatched Neuro2A tumors. These findings further validate the utility of targeting myeloid NF‐κB p50 as a strategy for cancer therapy and demonstrate activity of p50‐IMC generated by gene editing of syngeneic marrow cells, a cell product relevant to clinical translation. Abstract : Myeloid cells lacking NF‐κB p50 adopt a pro‐inflammatory M1 phenotype. Adoptive transfer of p50‐deficient immature myeloid cells (p50‐IMC), generated from either p50‐null mice or via gene editing, impedes the growth of murine neuroblastoma, dependent upon the presence of T cells and MHC‐mediated antigen presentation. Epigenetic therapy or T‐cell checkpoint inhibition cooperates with the absence of myeloid NF‐κB p50 to further slow tumor growth.